Investigation of material properties of masonry units used in brick walls - Yetkin, Musa; Alyamaç, Kürşat Esat; Calayır, Yusuf (My University, 2019)
Walls are used as load-bearing wall and partition wall in structures systems. In masonry structures, the walls are carriers. Load-bearing walls carry loads such as beams, columns, foundations and slabs. In some structures systems, walls are used only to separate spaces without carriers. In masonry structures where the walls are carriers, the masonry unit and the mortar unit are very important. If the properties of these two units are known correctly, the properties of the load-bearing wall can be estimated approximately. In this study, the studies that determine the material properties of the brick unit (compressive strength, dimensions, water absorption percentage and unit volume mass) experimentally will be examined in detail. An evaluation will be made between the studies for the change of each material properties. The relationship of different material properties with each other will also be studied.
Bildiri - Yayımlanmış
Keywords: Brick unit; Masonry structure; Material properties